Etnobotani Tumbuhan Obat oleh Masyarakat Desa Sungai Ulu Kabupaten Natuna - Suri, Linda Amelia; Syamswisna, Syamswisna; Mardiyyaningsih, Asriah Nurdini (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Sungai Ulu Village, East Bunguran District, Natuna Regency is a village where the people use plants as traditional medicine. It is necessary to document medicinal plants in order to increase awareness to preserve medicinal plants. The aim of this research is to conduct an ethnobotanical study of medicinal plants to determine the use of medicinal plants by the people of Sungai Ulu Village. This type of research is qualitative research with descriptive methods, with samples taken using snowball sampling techniques. The data collection technique uses triangulation, namely a combination of interviews, observation and documentation. The research results showed that there were 76 types of medicinal plants used by local communities, consisting of 45 families that could treat 41 types of diseases. The part of the plant that is most widely used is the leaves, while the habitus that is most commonly found is herbs with the most locations in home gardens, with the most processing and use method being boiled and then drunk.